(untitled) (Journal of Universal Science Research, 2025)
This article examines how literacy instruction affects the speech development of children aged 6-7 as well as the strategies and tactics employed in this process. The study’s objectives were to examine mastery indicators, offer suggestions for how to teach children to read, and enhance the speech abilities of preschool-aged children between the ages of six and seven through interactive used in the educational process to promote literacy and enhance the speaking, narrative, and vocabulary skills of children aged 6-7 as they prepared for school.